Effectiveness of the Quizizz Application in Improving Students' Reading Comprehension at SMP Darul Falah - Adi, Mohammad Sofyan; Khofi, Ahmad Zainul; Dimastiar, Moh. Ansori (International Journal of English Education and Linguistics (IJoEEL), 2024)
This research investigates the effectiveness of the Quizizz application in enhancing students' reading comprehension at SMP Darul Falah. A quasi-experimental design was employed, involving two groups of seventh-grade students: an experimental group using Quizizz and a control group utilizing Google Forms for learning recount texts. The methodology includes pre-tests and post-tests to measure reading comprehension, with statistical analysis conducted using SPSS. The findings reveal that the experimental group, which utilized Quizizz, exhibited significant improvement in reading comprehension compared to the control group. Normality and homogeneity tests confirm the reliability of the data, and the Mann-Whitney U test indicates a significant difference in outcomes between the two groups. Based on the study's results, it can be concluded that Quizizz is an effective medium for teaching reading comprehension, offering a more engaging and motivating learning experience compared to traditional methods. These findings suggest that incorporating interactive and gamified tools like Quizizz can greatly enhance educational practices and improve student performance in reading comprehension.